A Comparative Study of Interscalene Block Vs. Interscalene Block with Superficial Cervical Plexus Block for Clavicular Plating - Regmi, Nabin Kumar; Pokhrel, Kapil (Journal of Nepalgunj Medical College, 2019)
Background: Regional anaesthesia for fixation of clavicle fracture is a new concept. Various techniques of regional anaesthesia are being tried to find the optimal type. Combined interscalene and superficial cervical plexus block is widely accepted. Aim of Study: This study aims to compare the efficacy of interscalene block (ISB) with combined interscalene block and superficial cervical plexus block (ISB+ SCPB) for clavicular plating. Material and Methods: This prospective, hospital based comparative study was conducted from March 2019 to October 2019, in the department of anaesthesiology, Nepalgunj Medical College. 60 ASA category I and II patients undergoing clavicular plating and belonging to age group 16-65 years were enrolled. Patients were divided into two groups: Group I: ISB (n=30), Group II: ISB+ SCPB (n=30). Blocks were given using landmark technique. Primary outcome measures were conversion to general anesthesia (GA), requirement of supplemental analgesia and patient satisfaction. Secondary outcome measures were sensory and motor block, duration of analgesia and complications. These outcome measures were compared between the groups. Results: No patient required conversion to GA. The number of patient requiring supplemental analgesia was significantly higher in ISB group in comparison to ISB+ SCPB. Patient satisfaction was excellent in both groups. No statistically significant complications were seen in either group. Conclusion: Interscalene block combined with Superficial Cervical Plexus Block (ISB + SCPB) has better efficacy than Interscalene block (ISB) alone for clavicular plating. Nevertheless, both techniques avoid GA and provide excellent patient satisfaction level.